Rapid Weight Gain and Feeding Practices in the First 6 Months of Life Are Associated with Dysbiosis of the Gut Microbiome in Toddlerhood (P21-032-19). (13th June 2019) - Whisner, Corrie; Wyst, Kiley Vander; Petrov, Megan; McCormick, David; Todd, Michael; Reifsnider, Elizabeth
Abstract: Objectives: Nearly 10% of infants and toddlers carry excess weight for their length. Rapid weight gain (RWG; >+0.67 change in weight-for-age Z-score) and feeding practices from 0–6 months (mo) of life are strong determinants of obesity. Both RWG and feeding practices may influence the gut microbiome (GM), which in turn can affect obesity risk by increasing susceptibility to weight gain during infancy. Our goal was to evaluate differences in GM community structure at 36 months of age in relation to feeding practices and RWG in infancy. Methods: Pregnant, obese Latinas ( n  = 36) recruited from the Special Supplemental Nutrition Program for Women, Infants, and Children program took part in a larger randomized health education trial designed to prevent infant overweight. The intervention was delivered from 0–12 mo and participants were followed until 36 mo of age. At one, 6, and 12 mo, mothers reported infant feeding practices. RWG was categorized as >0.67 positive change in weight-for-age Z-score over the first 6 months of life. Microbial DNA from feces collected at 36 mo were sequenced using primers for the 16S rRNA gene V4 region. GM diversity metrics were examined using Kruskal-Wallis and PERMANOVA comparisons, adjusted for multiple comparisons, via Qiime2. Results: Of the cohort, 12 children experienced RWG in the first 6 mo of life. Within-sample species number (richness, Shannon Diversity Index: P  = 0.014) and evenness (Pielou's Index: P  = 0.019) were significantly lower at 3 years among children experiencing RWG in infancy. Upon comparing GM community structure (beta-diversity), exclusively breastfed infants ( N  = 9) formed a separate cluster from combination or formula-fed infants driven by phylogenetic diversity and species presence/absence (unweighted UniFrac: P  = 0.033; Jaccard: P  = 0.014). Children introduced to solid foods before ( N  = 30) vs. after ( N  = 6) 6 mo (Bray Curtis: P  = 0.056; weighted UniFrac: P  = 0.071). Conclusions: RWG and feeding practices in the first 6 mo of life appear to shape the GM in ways that last into toddlerhood. Identifying specific microbes may provide insights for intervention to prevent RWG. How shifts in the GM influence risk for childhood and adult obesity remain an area for exploration. Funding Sources: R01DK096488 and ASU Obesity Solutions, Virginia G. Piper Foundation.